Strengths-based counseling with at-risk youth - Ungar, Michael (Corwin Press, 2006)
Surviving and thriving : what at-risk youth do, and what we can begin to do better -- Understanding youth as three identities : pandas, chameleons, and leopards -- Six strategies to discover hidden strengths -- From truth to action : strategies two through five -- Meaningful substitutions : real options for real resilience -- A new way to look at bullying -- Assessing resilience -- Translating the results of the resilient youth strengths inventory -- Conclusion : the need for change.